Just Grace - Harper, Charise Mericle (Boston : Houghton Mifflin, 2007)
Misnamed by her teacher, seven-year-old Just Grace prides herself on being empathetic, but when she tries to help a neighbor feel better, her good intentions backfire.
Wilson's Children, January 2009
School Library Journal, June 2007
Book Links (A.L.A.), May 2007
Booklist starred, March 2007
Bulletin of the Center for Children's Books starre, July 2007
Publisher's Weekly, April 2007
Keywords: Empathy -- Juvenile fiction; Neighbors -- Juvenile fiction; Schools -- Juvenile fiction; Empathy -- Fiction; Neighbors -- Fiction; Schools -- Fiction; Empathy -- Fiction; Neighbors -- Fiction; School stories